Pengaruh Kualitas Produk dan Citra Merek Terhadap Kepuasan Konsumen Yamaha Nmax (Studi Kasus Pada PT. Yamaha Tjahaja Baru) - Riche Fermayani; Ash Shadiq Egim; Romi Rianto Harahap (Universitas Negeri Padang, 2021)
This study aims to determine the effect of product quality and brand image on consumer satisfaction Yamaha Nmax in Padang City (Case Study at PT. Yamaha Tjahaja Baru Padang). The samples examined in this study were 84 respondents who were consumers of Yamaha Nmax in Padang City. Based on the statistical t test performed, it can be concluded that the product quality variable has a positive and significant effect on customer satisfaction as indicated by the significance value of 0,000 < alpha 0.05. Based on the statistical t test performed, it can be concluded that the brand image has a positive and significant effect on customer satisfaction as indicated by the significance value of 0,000 < alpha 0.05. Based on the simultaneous f test obtained a significance value of 0,000 < 0,05, it can be concluded that product quality and overall brand image have a significant effect on consumer satisfaction on Yamaha Nmax in Padang City. The magnitude of the influence of the independent variable on the dependent variable is 74.8%, the remaining 25.2% is influenced by other variables not included in the research model.Keywords: Product Quality, Brand Image, and Consumer Satisfaction